The Demographical Analysis Of Indonesian Buy-Now-Pay-Later Users Financial Wellbeing - Daffa Kenian Irsya; Taufik Faturohman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to understand what causes financial wellbeing among Indonesian Buy-Now-Pay-Later Users in terms of demographical. A survey from 400 respondents was collected through an online questionnaire from January to June 2024 and analyzed using descriptive statistics, and continued by using Kruksal Wallis and Mann Whitney U in SPSS to test whether there is a statistically significant difference between two or more independent variables. This study is confirmed as the study demonstrates that demographic factors significantly influence financial well-being. These insights emphasize the importance of considering demographic variables when assessing financial health and tailoring financial education, policy-making, and service provision to effectively address the diverse needs of different demographic groups.